2022
DOI: 10.53738/revmed.2022.18.783.1048
|View full text |Cite
|
Sign up to set email alerts
|

Tissu adipeux épicardique et fibrillation auriculaire

Abstract: La fibrillation auriculaire (FA) est l'arythmie la plus fréquemment rencontrée chez l'adulte ; elle est associée à une morbi-mortalité importante. L'obésité est un facteur de risque contribuant à sa survenue. Récemment, l'intérêt s'est porté sur le tissu adipeux épicardique (TAE), défini comme un dépôt adipeux situé entre l'épicarde et le péricarde viscéral. Ses caractéristiques sont distinctes des dépôts adipeux classiques : il infiltre le myocarde épicardique et sécrète des cytokines modulant l'électrophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“… 80 Increased EAT thickness is an independent predictor of AF and associated with the severity and recurrence of AF. 81 In patients with RA, EAT thickness is higher than in healthy controls. 82 Furthermore, EAT thickness is positively correlated with the severity of RA.…”
Section: Pathophysiological Pathways Between Ra and Afmentioning
confidence: 97%
See 1 more Smart Citation
“… 80 Increased EAT thickness is an independent predictor of AF and associated with the severity and recurrence of AF. 81 In patients with RA, EAT thickness is higher than in healthy controls. 82 Furthermore, EAT thickness is positively correlated with the severity of RA.…”
Section: Pathophysiological Pathways Between Ra and Afmentioning
confidence: 97%
“…[28][29][30]124 The major pathophysiological mechanisms of AF include atrial remodeling, autonomic nervous system dysfunction, activation of RAS, endothelial dysfunction, increased EAT thickness, higher adiponectin concentrations and IR. 31,32,53,55,62,68,69,81,84 RA is widely involved in these pathophysiological processes. Controversially, some studies have shown an absence of association between RA and the occurrence of new-onset AF.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Эпикардиальная жировая ткань (ЭЖТ) располагается между висцеральным перикардом и поверхностью эпикарда. Увеличение толщины ЭЖТ является независимым предиктором ФП и связано с тяжестью и рецидивами ФП [59]. У пациентов с РА толщина ЭЖТ выше, чем у здоровых людей [60].…”
Section: фибрилляция предсердий и другие потенциальные сердечно-сосуд...unclassified